Preparedness Response of Indonesian Tax Offices Concerning the Zakat as a Taxable-Income Deduction - Dodik Siswantoro; Sri Nurhayati (Center of Strategic Studies (PUSKAS) BAZNAS, 2016)
This paper aims to analyze the preparedness response of tax offices on the issue of the zakat as a taxable-income deduction. Act No. 17/2000, at the top level, and Government regulation No. 60/2010 supports this policy in detail. However, many people do not claim restitution regarding this policy. This paper uses primary data gathered from phone interviews. Seven tax offices, including service centers, were interviewed in March 2012. The paper provides evidence that each tax office had different responses, provided less information, and acted unsupportive on the issue. In addition, the process of restitution for tax claims is difficult and unfavorable from the zakat payer’s perspective. New tax regulations must be supported by clear information socialization and efficient tax restitution process from tax the office. Otherwise, it would not be effective as the benefits may be smaller than the effort. Keywords: Zakat, tax office, response, Indonesia, preparedness